Friends and family: A literature review on how high school social groups influence advanced math and science coursetaking - Gottfried, Michael; Owens, Ann; Williams, Darryl; Kim, Hui Yon; Musto, Michela (Education Policy Analysis Archives, 2017)
In this study, we synthesized the literature on how informal contexts, namely friends and family social groups, shape high school students’ likelihood of pursuing advanced math and science coursework. Extending scholarly understandings of STEM education, we turned to the body of literature with three guiding questions: (1) What influence do friends have on advanced math and science coursetaking? (2) What influence does family, particularly parents, have on advanced math and science coursetaking? (3) Do the effects vary by gender among each social group? By synthesizing existing literature on the influence of family and friends on advanced math and science coursetaking in high school, we find that both friends and families can influence the number of advanced math and science courses students complete, but the amount of advanced coursework students complete also varies based on the gender of the individual student, the gender of his/her friends, as well as by mother or father. Implications and limitations are discussed.